Teaching “Global Learning” through the Ecotestimonio: Ojos negros by Eduardo Sguiglia in Class - Laura Barbas-Rhoden (Studies in 20th & 21st Century Literature, 2015)
This essay uses Eduardo Sguiglia’s Ojos negros (‘Black Eyes,’ 2010), a border-crossing, transnational ecotestimonial novel, to demonstrate step-by-step how instructors can effectively use ecotestimonial narratives in teaching undergraduate students to achieve global learning outcomes. Ecotestimonial texts prompt readers, and especially those readers removed from problems depicted, to confront the multiple facets of wicked problems of environmental degradation and to become aware of how the representation (or lack of representation) of those problems in different contexts shapes social responses to them. By moving students intentionally from comprehension of narrative and context to a focus on higher order thinking and on the process by which one interacts with a text and with others, instructors of humanities classes can create course units in which students both meet global learning outcomes and reflect upon the process by which they have done so.
Keywords: ecocriticism; ecotestimonio; Latin American literature; pedagogy; global learning; Ojos Negros; Eduardo Sguiglia